The role of activity of Orthodox parish clergy in Belarus during the Nazi occupation (1941–1944) - Silova, Svetlana V. (Journal of the Belarusian State University. History, 2019)
On the basis of documents from various archives, little-known pages of the history of the Orthodox Church in Belarus during the Great Patriotic War are being investigated. The main directions of activity of the Orthodox clergy during the years of the Nazi occupation, previously not of interest to the national historical science, are revealed. The author reflects the role of individual priests in the normalization and development of parish life and the salvation of parishioners. The examples show the forms of interaction of the Orthodox clergy with partisan and underground movements, the problems of relations with representatives of the occupying power and collaboration.
Keywords: Belarus; occupation; Orthodox clergy; parish life; guerrilla movement; Great Patriotic War